IMPLEMENTASI SISTEM INFORMASI AKUNTANSI (SIA) DALAM MENINGKATKAN TRANSPARANSI PENGELOLAAN KEUANGAN BADAN USAHA MILIK DESA (BUMDES) ASTAGINA - Ainiyah, Ghonimah Zumroatun (Medikonis, 2022)
The existence of relatively large assets in BUMDes Astagina both from APBDes capital participation, partnerships and the results obtained, then in financial management must be able to apply the established SIA, with the aim of making it easier for managers and having an impact on financial statement accountability. However, until now the financial management of BUMDes Astagina has not implemented SIA, so the transparency process has not been optimal. This study aims to determine the obstacles and actions that must be taken immediately in an effort to implement SIA to increase the financial transparency of BUMDes.This type of research is descriptive qualitative with a case study design. The technique of determining the informants using purposive sampling. All data collected in this study were obtained by conducting interviews at BUMDes Astagina, Pagak Village, Purwareja Klampok District, Banjarnegara Regency. The technique used in data examination is data triangulation.The results showed that the BUMDes Astagina managers had attended SIA implementation training organized by BRI together with bumdes.id in collaboration with syncore genio which was carried out online through a zoom meeting. From the implementation of the training, until now there has been no follow-up, both assistance from the organizers and managers of BUMDes have not implemented SIA in the preparation of financial reports. This happened because the BUMDes managers still did not understand and there were difficulties in accessing the SIA in the form of the SAAB.Syncore application. This affects the effectiveness and efficiency of the preparation of financial reports and the transparency process which results in the low support, trust and enthusiasm of the village community for the implementation of the Astagina BUMDes programs.